Analisis Hukum Onrechtmatige Daad dalam Perjanjian Jual Beli Tanah Warisan yang Dijual Secara Sepihak Menurut Kitab Undang-Undang Hukum Perdata - Adelina Sitanggang; Joy Prana Bangun; Mira Cahya; Martua Felix Jonathan; Nur Hidayah Hasibuan; Nasywa Yasmin Purba; Sri Hadiningrum; Parlaungan Gabriel Siahaan (Departement of Mathematics Education, 2024)
This analysis aims to explore the legal concept of onrechtmatige daad (act against the law) in the context of a sale and purchase agreement for inherited land that is sold unilaterally according to the Civil Code. The main focus of this analysis is to determine whether the act of unilaterally selling inherited land can be categorized as onrechtmatige daad based on the applicable civil law provisions. This research involves analysis of various relevant articles and court decisions to gain a comprehensive understanding of this issue. It is hoped that the results of this analysis can contribute to enriching understanding of the legal protection of inheritance rights in the context of land sale and purchase agreements according to civil law in Indonesia.In carrying out this analysis, the relevance of court decisions related to similar cases is crucial. Analysis of these decisions will provide an overview of how the law of onrechtmatige daad is applied in the context of a unilateral sale and purchase agreement for inherited land. Through this approach, patterns of court decisions can be identified that can illustrate how civil law is interpreted in similar cases, and how legal considerations are considered in the relevant context.It is hoped that the results of this analysis can contribute to enriching understanding of the legal protection of inheritance rights in the context of land sale and purchase agreements according to civil law in Indonesia.